2017
DOI: 10.1523/jneurosci.3392-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Directed Visual Processing Differentially Impacts Human Ventral and Dorsal Visual Representations

Abstract: Recent studies have challenged the ventral/"what" and dorsal/"where" two-visual-processing-pathway view by showing the existence of "what" and "where" information in both pathways. Is the two-pathway distinction still valid? Here, we examined how goal-directed visual information processing may differentially impact visual representations in these two pathways. Using fMRI and multivariate pattern analysis, in three experiments on human participants (57% females), by manipulating whether color or shape was task-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 79 publications
5
92
2
Order By: Relevance
“…4). As was previously observed (Vaziri-Pashkam et al, 2017), the task-and category-related information were dominant in the frontoparietal and occipitotemporal cortices, respectively. The current study, extended these results by investigating the flow of task-and category-related information in the brain and showed that the processing of target-related information was initiated on prefrontal areas and the information was sent to posterior brain areas probably for facilitated decision-making and recognition (Bar et al, 2006;Summerfield et al, 2006).…”
Section: Spatiotemporal Dynamics Of Category-and Target-related Inforsupporting
confidence: 82%
See 2 more Smart Citations
“…4). As was previously observed (Vaziri-Pashkam et al, 2017), the task-and category-related information were dominant in the frontoparietal and occipitotemporal cortices, respectively. The current study, extended these results by investigating the flow of task-and category-related information in the brain and showed that the processing of target-related information was initiated on prefrontal areas and the information was sent to posterior brain areas probably for facilitated decision-making and recognition (Bar et al, 2006;Summerfield et al, 2006).…”
Section: Spatiotemporal Dynamics Of Category-and Target-related Inforsupporting
confidence: 82%
“…In order to gain a deeper insight into the spatiotemporal dynamics of object and task processing, a recent study, which fused MEG with functional magnetic resonance imaging (fMRI), found that a sequence of overlapping and separate structures along the frontoparietal and occipitotemporal cortices undertook task processing (Hebart et al, 2018). This observation was on par with previous findings which suggested that task processing was distributed along both the dorsal and ventral visual streams (Vaziri-Pashkam and Xu, 2017). They found a late effect of task when decoded the brain signals with ignorable influence of task on object representations (Hebart et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Substantial evidence from electrophysiological (Toth and Assad, 2002;Freedman and Assad, 2006;Ibos and Freedman, 2014) and BOLD Erez and Duncan, 2015;Bracci et al, 2017;Vaziri-Pashkam and Xu, 2017;Long and Kuhl, 2018) measurements indicates that LPC representations of perceptual events are influenced by top-down goals. Our results provide novel evidence that, in dorsal LPC, specific features of a remembered stimulus are dynamically strengthened or weakened according to the current goal.…”
Section: Influence Of Retrieval Goals On Lpc Representationsmentioning
confidence: 99%
“…In particular, adaptive coding properties have been demonstrated in a set of parietal and frontal regions that are collectively referred to as the Multiple-Demand (MD) network (Duncan, 2010;Fedorenko, Duncan, & Kanwisher, 2013;Mitchell et al, 2016). Some sub-regions of the MD network have been previously shown to encode information about abstract task rules and response mappings (Harel, Kravitz, & Baker, 2014;Waskom, Kumaran, Gordon, Rissman, & Wagner, 2014;Woolgar, Thompson, Bor, & Duncan, 2011), as well as representations of relevant visual object properties (Y. Erez & Duncan, 2015;Jackson, Rich, Williams, & Woolgar, 2017;Vaziri-Pashkam & Xu, 2017). Though its role in invariant target recognition has not yet been tested, based on these coding properties, the MD network may play an important role in recognizing relevant objects during search, especially when successful search relies on flexibly updating the set of features that define the current target.…”
Section: Introductionmentioning
confidence: 99%